2005
DOI: 10.1080/03091900512331333158
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on medical infrared imaging

Abstract: Since the early days of thermography in the 1950s, image processing techniques, sensitivity of thermal sensors and spatial resolution have progressed greatly, holding out fresh promise for infrared (IR) imaging techniques. Applications in civil, industrial and healthcare fields are thus reaching a high level of technical performance. The relationship between body temperature and disease was documented since 400 bc. In many diseases there are variations in blood flow, and these in turn affect the skin temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
131
0
18

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(155 citation statements)
references
References 28 publications
0
131
0
18
Order By: Relevance
“…Since there is a high degree of thermal symmetry in the normal body, subtle abnormal temperature asymmetry's can be easily identified 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Since there is a high degree of thermal symmetry in the normal body, subtle abnormal temperature asymmetry's can be easily identified 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…There are clear indications that thermography is a valid (Ammer and Ring, 2008;Zaproudina et al, 2006) technology, which is both non-invasive and low-cost, that rapidly produces a non-contact recording of the energy irradiated from the body (Han et al, 2010;George et al, 2008;Jiang et al, 2005). It has been recently shown that a high resolution thermal image can provide interesting information about the complex thermoregulation system of the body (Pascoe el al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are commonly associated with regional vasodilation, hyperthermia, hyperperfusion, hypermetabolism, and hypervascularization (27)(28)(29), which generate a highertemperature heat source. Unlike imaging techniques such as X-ray, ultrasonography, MRI, and other structural imaging tools that primarily provide information on the anatomical structures, infrared imaging provides functional information that is not easily measured by other methods.…”
Section: Figure 2 Image Of Breast Ultrasonographymentioning
confidence: 99%